Ductility of RC beams under torsion. (1st August 2018) - Teixeira, M.M.; Bernardo, L.F.A.
Highlights: The torsional ductility of RC beams with rectangular cross section is studied. A torsional ductility index is defined to characterize the torsional ductility. The influence of important variable studies is studied and discussed. A comparative analysis with the rules from some codes of practice is performed. Some codes are too much restrictive as far as torsional ductility is concerned. Abstract: In this article, the torsional ductility of reinforced concrete (RC) beams with rectangular cross section is studied. For this, the experimental results of several RC beams found in the literature were compiled and analyzed. A torsional ductility index was used to characterize the torsional ductility of the studied beams. The following variables study were considered: compressive concrete strength, torsional reinforcement ratio and cross section type (plain or hollow). The influence of each variable study on the torsional ductility is studied and important findings are pointed out which could help for the design of RC beams under torsion. An additional comparative analysis with the rules from some codes of practice in use is also performed. It is shown that, in general, the codes are too much restrictive as far as the maximum torsional reinforcement is concerned. As a consequence, this can leads to the unacceptance of several beams with ductile behavior.